Setting Families Up for Success: A Pilot Study of a Toolkit to Enhance the Autism Spectrum Disorder Diagnostic Evaluation Process. - Haine-Schlagel, Rachel; Corsello, Christina; Caplan, Barbara; Gould, Hilary; Brookman-Frazee, Lauren (Journal of Autism & Developmental Disorders, 2024)
Families of children with autism spectrum disorder (ASD) face challenges engaging in services following diagnosis. This study: (1) developed and implemented a toolkit to tailor ASD evaluation feedback to families' needs, and (2) evaluated caregiver and provider perceptions of the toolkit. Focus groups with providers (N = 11) informed toolkit development. Seven providers participated in pilot training and implementation. Provider and caregiver toolkit perceptions were assessed using interviews, surveys, and a fidelity checklist. Toolkit strategies reflect focus group themes. Provider and caregiver ratings suggest the initial feasibility, acceptability, and utility of the toolkit. This toolkit may be feasible to implement in community settings and may increase caregiver satisfaction, though further refinements are needed to support service connection.